Optimization in additive manufacturing - Camelo, Wesley Fernandes (2018)
Additive Manufacturing is a mechanical productive process whose utilization is increasing rapidly. This dissertation was focused in the topological optimization of mechanical parts with a view to reduce their weight, keeping or increasing their mechanical strength. Two different parts usually obtained by conventional techniques were used as case studies, being applied successive iterations leading to their optimization, regarding the use of Additive Manufacturing to produce them in the future. The optimization allowed for parts weight reduction, which will contribute to the always wanted global weight reduction of the set where they belong, improving the sustainability and reduction of emissions. The Altair Hypermesh software was used exclusively as an instrument for performing optimizations.